Extraction of anthocyanins and other phenolics from dried blackcurrant (Ribes nigrum L.) pomace via ultrasonication - Mohamed Nawawi, Nur Izzati; Ahmad Khushairi, Nur Allisya Akma; Ijod, Giroon; Mohamad Azman, Ezzat (Elsevier, 2025)
Blackcurrant (Ribes nigrum L.) pomaces are rich in phenolic compounds, particularly anthocyanins yet often discarded as waste during juice processing. The heat-sensitive phenolic compounds such as anthocyanins, unavoidably, degrade due to higher temperatures and longer times during conventional extraction methods. Typically, organic solvents such as ethanol, methanol, and acetone were used to extract the phenolic compounds from dried blackcurrant pomaces (DBP). The necessity for employing substantial amounts of solvents in conventional extraction methods, such as water baths, resulted in health hazards and environmental pollution. Hence, this study aimed to investigate the effect of ultrasonication (US) and water bath (WB) extraction time on the anthocyanins composition, total phenolic content (TPC), total flavonoid content (TFC), and antioxidant activity of DBP extracts. The DBP powders were mixed with 50 % ethanol in the beaker (1:40, w/v) and extracted for 5 − 30 min using ultrasonication at 50 % amplitude and a water bath at 180 rpm. The extracts were further analyzed using the HPLC analysis, Folin-Ciocalteu method, flavonoid content, DPPH, and FRAP assays. As a result, ultrasonication only required 10 min to produce ∼27 % higher total anthocyanins (37.15 ± 0.71 mg/g) than the water bath at 20 min (26.97 ± 0.18 mg/g), while the highest TPC (38.02 ± 0.24 mg GAE/g) and TFC (38.83 ± 1.41 mg CE/g) were recorded at 20 min. Also, a significantly higher (p < 0.05) DPPH inhibition (52.76 ± 0.90 %) and reducing power (352.60 ± 7.64 µmol TE/g) were detected after 25 min of ultrasonication. Overall, ultrasonication is suitably used as an alternative to conventional extraction, where the natural colorant obtained from DBP extracts could be potentially utilized in commercial food applications. © 2025 The Authors